I3− entrapped cationic Zn(ii) coordination polymer: selective detection and dose-dependent photocatalytic degradation of roxithromycin - Sharma, Preeti; Musheer Ahmad; Haq, Nazrul; Kafeel Ahmad Siddiqui (CrystEngComm, 2024)
This study presents the synthesis and characterization of a new zinc-based coordination polymer, {[Zn(BPMEDA)I]2+·2I3−}n (zinc-CP), utilizing Zn(ii) ions and the N,N′-bis(2-pyridylmethyl)-1,2-ethylenediamine tetrahydrochloride dihydrate (BPMEDA) ligand. Powder X-ray diffraction (PXRD), Fourier-transform infrared spectroscopy (FTIR), single-crystal X-ray diffraction (SCXRD), energy-dispersive X-ray spectroscopy (EDAX), scanning electron microscopy (SEM), and elemental mapping confirmed zinc-CP's structural integrity and composition. Furthermore, we assessed the stability of our crystal at different pH levels and evaluated its water stability by immersing the crystal in water over several days. The photoluminescence detection capability of zinc-CP was investigated with nine different antibiotics, revealing that the macrolide antibiotics, roxithromycin (RXM) and azithromycin (AZM), exhibited the highest limits of detection (LOD). Additionally, the photocatalytic degradation phenomenon of zinc-CP was assessed for the same antibiotics, demonstrating remarkable degradation rates of 97.59% for sulfadiazine (SDZ) and 94.52% for RXM. These findings demonstrate zinc-CP's potential as a sensitive sensor and photocatalyst for environmental pharmaceutical contaminants. Zinc-CP can identify and degrade pharmaceutical pollutants like antibiotics, indicating its potential for environmental cleanup. Zinc-CP's sensitive detection and catalytic breakdown make it a promising material for controlling pharmaceutical waste in water and other ecosystems in an environmentally responsible manner.